Discussion on Maritime Entitlements of “Disappearing Islands” Under the Situation of Rising Sea Level - Lei Wang (Studies in Law and Justice, 2023)
The impact of climate change-induced sea-level rise has been increasing in recent years. Recent estimates by the United Nations Intergovernmental Panel on Climate Change indicate that sea levels will rise by 98 centimeters by 2100—a considerable increase from the 59 centimeters predicted in 2007. As sea levels continue to rise, the land area of islands shrinks or is even submerged, creating “disappearing islands”. On land, habitats are destroyed, endangering species and threatening coastal investments such as coastal cities and harbors; on the sea, low-tide lines may be altered, inundating important baselines, with boundaries advancing or retreating in tandem with the baselines that have been drawn. The “disappearing islands” will no longer be a remote issue.